2017
DOI: 10.1002/jum.14376
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Complications of Extracranial Carotid Artery Interventions

Abstract: Carotid endarterectomy and carotid artery stenting are among the most common peripheral vascular procedures performed worldwide. Sonography is the initial and often only imaging modality used in the evaluation of iatrogenic carotid arterial injuries. This pictorial essay provides an overview of the clinical and sonographic findings of complications after interventions in the extracranial carotid arteries, including dissection, fluid collections, pseudoaneurysm, thrombosis, thromboembolism, restenosis, and sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…CAS is an effective treatment for carotid artery stenosis[ 6 - 9 ]. However, embolism is one of the most common and serious complications during the perioperative period[ 10 ]. A clinical study, which retrospectively analyzed 19826 consecutive patients who underwent DSA, showed that embolic complications occurred in 0.05% of all patients[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAS is an effective treatment for carotid artery stenosis[ 6 - 9 ]. However, embolism is one of the most common and serious complications during the perioperative period[ 10 ]. A clinical study, which retrospectively analyzed 19826 consecutive patients who underwent DSA, showed that embolic complications occurred in 0.05% of all patients[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CREST (Carotid Revascularization Endarterectomy vs Stenting Trial) and other studies showed that CAS had the same effect as CEA in treating symptomatic and asymptomatic carotid stenosis, and there was no significant difference in the incidence of overall postoperative complications even though CAS was less invasive than CEA[ 6 - 9 ]. Embolism is a common complication after CAS, which is usually reported as nervous system embolism[ 10 ]. However, no cases of ileal hemorrhagic infarction caused by mesenteric artery embolism after CAS have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Carotid endarterectomy in neurosurgery can effectively prevent plaque-sheddinginduced stroke and ischemic cerebrovascular diseases. However, intimal denudation results in intimal injury and thinning of the blood vessel wall, which can cause arterial dissection [27,28]. It is crucial to closely monitor such patients and prevent excessive intimal damage.…”
Section: Novel Animal Model In Carotid Artery Dissectionmentioning
confidence: 99%
“…CDU and TCCS are recommended following carotid revascularization procedures for the immediate and long‐term follow‐up. Soon after recanalization, carotid duplex examination is performed for the screening of possible complications such as dissections, fluid collections, pseudoaneurysm formation, thrombosis at the site of the treated stenosis, restenosis, and stent thrombosis …”
Section: Neurosonology Applications In Postoperative Monitoringmentioning
confidence: 99%
“…On the other hand, wound abscesses deriving from superinfections of hematomas are rare . Hematomas are recognized on gray‐scale carotid ultrasounds as soft tissue masses with heterogeneous echogenicity, with no flow within on color duplex . The formation of pseudoaneurysms is also a rare complication of CEA, occurring in less than .4% of cases, and results from rupture of the entire vessel wall and the subsequent tamponade of the hematoma from adjacent tissues .…”
Section: Neurosonology Applications In Postoperative Monitoringmentioning
confidence: 99%